A computational study of biomagnetic fluid flow in a channel in the presence of obstacles under the influence of the magnetic field generated by a wire carrying electric current. Issue 4 (4th July 2018) - Mousavi, S. Morteza; Farhadi, Mousa; Sedighi, Kurosh
ABSTRACT: In this paper, biomagnetic fluid flow in a three-dimensional channel in the presence of obstacles and under the influence of a magnetic field is studied numerically. The magnetic field is generated by a wire carrying electric current. The mathematical model of biomagnetic fluid dynamics which is consistent with the principles of ferrohydrodynamics and magnetohydrodynamics is used for the problem formulation. A computational grid which accurately covers the magnetic force is used for the discretisation of computational domain. The flow field is studied in the different arrangements of the obstacles and diverse magnetic field strengths. The results show that the flow pattern is drastically influenced by the applied magnetic field. Applying the magnetic field causes a secondary flow that affects the velocity distribution considerably. The magnetic force also reduces the maximum axial velocity. Furthermore, the magnetic field has a considerable impact on the recirculation zones behind the obstacles. The magnetic field makes the recirculation zones smaller. This study indicates that applying the magnetic field increases the axial drag coefficients of the obstacles significantly (in a case, by 40.15%).